Critical Reflection as a Key Component of Personalized Language Learning in Digital Education Environment at University - Lavrysh, Yuliana; Korbut, Oksana; Buha, Svitlana (Pedagogical Discourse, 2021)
The article presents the problem of foreign languages personalized learning skills formation at the university. From the perspective of the issue, authors disclose an analysis of didactic conditions for the effective formation of foreign languages personalized learning skills formation. The main conditions are the skills of self-assessment and self-reflection, which help students identify their own educational needs, priorities, strengths and weaknesses. In the article, the authors offer their own understanding of critical reflection and the strategy of its formation. In order to obtain data for the analysis, the authors conducted a survey of foreign language teachers at the university, pedagogical observation of classes and analysis of literature on this topic. The research methods made it possible to identify key challenges that prevent the effective development of critical reflection skills. During the pedagogical observations, the authors identified and described in the article effective tools for the formation of critical reflection, in particular digital educational resources. It has been proven that the use of digital educational resources increases students’ motivation for self-reflection and adds interactivity and multimodality to the learning process. The unity of didactic and technological approaches is a fundamental didactic principle, on the basis of which the authors propose to form the skills of critical reflection.